(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2018)
The public security agencies of the member states must be maintained by public tax revenues, among other non-tax appropriations, because they constitute universal and general services, i.e. indivisible and non-specific, benefiting and protecting the community in general. On the basis of this thesis, on May 24, 2017, the Federal Supreme Court, in Extraordinary Appeal 643.247/SP, ruled that the fee for combating accidents, instituted by municipal law, was unconstitutional. Undoubtedly, the broad activity of preventing and fighting fires, resulting from a general police power, undertaken by the military fire departments - public security bodies of the member states - should be financed by state tax revenues. But the state tax is legitimate when its taxable event is the special inspection and control activity resulting from a specific police power carried out by the military body, because it constitutes a divisible and specific public service. In view of the declaration of unconstitutionality of the tax and in line with the case law of the STF and STJ, the right arises to the return of the credit for undue payment to the Municipal and State Treasuries.